2000
DOI: 10.1128/mcb.20.11.3795-3806.2000
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of S-Phase-Promoting Factors: Yeast Dbf4-Cdc7 Kinase Requires Prior S-Phase Cyclin-Dependent Kinase Activation

Abstract: In all eukaryotes, the initiation of DNA synthesis requires the formation of prereplicative complexes (pre-RCs) on replication origins, followed by their activation by two S-T protein kinases, an S-phase cyclindependent kinase (S-CDK) and a homologue of yeast Dbf4-Cdc7 kinase (Dbf4p-dependent kinase [DDK]). Here, we show that yeast DDK activity is cell cycle regulated, though less tightly than that of the S-CDK Clb5-Cdk1, and peaks during S phase in correlation with Dbf4p levels. Dbf4p is short-lived throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
105
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 80 publications
5
105
0
Order By: Relevance
“…Therefore, phosphorylation of Mcm2 by CDK generates at least two additional phosphorylation sites ( 26 S and 40 S) for Cdc7 kinase. Previous in vivo studies in S. cerevisiae also suggested that the sequential action of CDK and Cdc7 kinase is essential for the initiation of DNA replication (25). During S phase, Cdc7 kinase supports DNA replication only after CDK activation.…”
Section: S Pombementioning
confidence: 96%
“…Therefore, phosphorylation of Mcm2 by CDK generates at least two additional phosphorylation sites ( 26 S and 40 S) for Cdc7 kinase. Previous in vivo studies in S. cerevisiae also suggested that the sequential action of CDK and Cdc7 kinase is essential for the initiation of DNA replication (25). During S phase, Cdc7 kinase supports DNA replication only after CDK activation.…”
Section: S Pombementioning
confidence: 96%
“…immediately prior to replication origin firing). However, under these conditions, cells are budded, indicating that G 1 -S cyclins have been activated (36) and furthermore present S phase-specific cyclin-dependent kinase activity (37).…”
Section: Initiation Of Dna Replication Is Necessary For Manifestationmentioning
confidence: 99%
“…The preRC renders chromosomes competent for initiation of DNA replication, but initiation does not occur because cells have not yet committed to S phase. Both cyclin-dependent protein kinases (CDKs; Cdc28p-Clb5p and -Clb6p) and Cdc7p-Dbf4p are required for S phase commitment by activating origin firing and promoting loading of Cdc45p (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: T He Initiation Of Dna Replication In Saccharomyces Cerevisiaementioning
confidence: 99%